Bioactive Products From Plant-Endophytic Gram-Positive Bacteria - Ek-Ramos, María J.; Gomez-Flores, Ricardo; Orozco-Flores, Alonso A.; Rodríguez-Padilla, Cristina; González-Ochoa, Guadalupe; Tamez-Guerra, Patricia (Frontiers in Microbiology, 2019)
Endophytes constitute plant-colonizing microorganisms in a mutualistic symbiosis relationship. They are found in most ecosystems reducing plant crops’ biotic and abiotic stressors by stimulating immune responses, excluding plant pathogens by niche competition, and participating in antioxidant activities and phenylpropanoid metabolism, whose activation produces plant defense, structural support, and survival molecules. In fact, metabolomic studies have demonstrated that endophyte genes associated to specific metabolites are involved in plant growth promotion (PGP) by stimulating plant hormones production such as auxins and gibberellins or as plant protective agents against microbial pathogens, cancer, and insect pests, but eco-friendly and eco-safe. A number of metabolites of Gram-positive endophytes isolated from agriculture, forest, mangrove, and medicinal plants, mainly related to the Firmicutes phyla, possess distinctive biocontrol and plant growth-promoting activities. In general, Actinobacteria and Bacillus endophytes produce aromatic compounds, lipopeptides, plant hormones, polysaccharides, and several enzymes linked to phenylpropanoid metabolism, thus representing high potential for PGP and crop management strategies. Furthermore, Actinobacteria have been shown to produce metabolites with antimicrobial and antitumor activities, useful in agriculture, medicine, and veterinary areas. The great endophytes diversity, their metabolites production, and their adaptation to stress conditions make them a suitable and unlimited source of novel metabolites, whose application could reduce agrochemicals usage in food and drugs production.